STUDI PERBANDINGAN SPEKTRUM RESPONS DESAIN SNI 1726:2019 TERHADAP SNI 1726:2012 DI PROVINSI SUMATERA UTARA - Sitompul, Mizanuddin; Pasaribu, Hadianti Muhdinar; Oktaviani, Tetra (JURNAL TEKNIK SIPIL, 2022)
Currently, seismic load code for building and other structures SNI 1726:2019 have been enacted as a revision of SNI 1726:2012. Based on earthquake maps on both standards, North Sumatra is one of the provinces located in the earthquake area with high intensity. From the results of previous studies found changes in the spectrum design responses due to the establishment of SNI 1726:2019 as a revision of SNI 1726:2012 in Indonesia. Researchers are interested in discussing this change by reviewing 33 cities / regencies in North Sumatra Province. The results showed that there were changes in the site coefficients Fa and FV, spectral acceleration parameters SS, S1, SDS, and SD1 in most of the cities reviewed. In addition, there is also an anomalous phenomenon that occurs in the cities / regencies with Ss 0.8 g.